Does high-quality auditing decrease the use of collateral? Analysis from the perspective of lenders' self-protection - Yang Yang (China Journal of Accounting Research, 2014)
We examine the association between audit quality and the use of collateral in a sample of Chinese firms from 2005 to 2011. Using the full sample, we document a negative relationship between audit quality and the use of collateral that is consistent with lenders' interests. We also show that audit quality and collateral are regarded as alternative means of reducing debt credit risk. Our conclusions are robust after using an auditor-switching test, the Heckman two-stage model and a propensity-score matching model to address endogeneity issues. China's institutional background is also considered. First, we find that in the group of firms in which large shareholders are able to control borrowers' activities, the substitution effects between collateral and audit quality are reduced when the degree of separation between large shareholders' control and ownership is high. Second, these substitution effects are greater when the borrowers' ultimate controller is a state-owned enterprise (SOE) rather than a non-state-owned enterprise (NSOE). Third, the differences in substitution effects between NSOEs and SOEs are smaller in areas with a high market-development index. We conclude that the substitution effects are smaller in high credit risk firms than in low credit risk firms.
Keywords: 650; Credit risk; Loan collateral; Audit quality; Ownership structure